Bilateral vision loss on programmed hemodialysis (clinical observation) - Kaloshina, A A; Andreeva, N A; Zhorzholadze, N V; Kalashnikova, A K; Sheremet, N L (Vestnik oftal'mologii, 2022)
The most common complication of hemodialysis is blood pressure decrease, which is an ischemic optic neuropathy risk factor. The article presents a case study of sequential bilateral ischemic optic neuropathy with the development of amaurosis as a result of arterial hypotension against the background of programmed hemodialysis. Differential diagnosis in bilateral visual impairment is discussed.The most common complication of hemodialysis is blood pressure decrease, which is an ischemic optic neuropathy risk factor. The article presents a case study of sequential bilateral ischemic optic neuropathy with the development of amaurosis as a result of arterial hypotension against the background of programmed hemodialysis. Differential diagnosis in bilateral visual impairment is discussed.